Long-life valve control type power storage battery positive electrode lead paste formula and preparation method

By using a composite conductive polymer binder in the positive electrode of the lead acid battery, the problem of softening and falling off during the circulation process is solved, and the cycle stability and life of the battery are improved.

CN119673976AInactive Publication Date: 2025-03-21JIANGSU LEOCH BATTERY

Patent Information

Application Number
CN202411737520.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the circulation of lead-acid batteries, the "pulsation" of the volume of lead paste causes the binding between the active substances to gradually weaken, and the active substance network structure becomes loose, resulting in softening, shedding, capacity decay and poor circulation performance of lead paste.

Method used

The positive lead paste formula of a long-life valve-controlled power battery containing a composite conductive polymer binder is used to combine materials such as PEDOT:PSS and CMC into a composite conductive polymer binder to form a crosslinked structure, thereby enhancing the bonding force between the positive electrode active substances and between the positive electrode active substances and the plate gate.

Benefits of technology

It improves the charging acceptance ability of the positive electrode active substance, enhances the stability and cycle stability of the positive electrode structure, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673976A_ABST
    Figure CN119673976A_ABST
Patent Text Reader

Abstract

The invention provides a long-life valve control type power storage battery positive electrode lead paste formula containing a composite conductive polymer binder. The formula comprises the following components: lead powder; wherein the lead powder contains the following components in percentage by weight: 2%-5% of red lead, 8%-12% of pure water, 9%-13% of dilute sulphuric acid, 0.15%-0.3% of high-purity graphite, 0.07%-0.15% of super-strong polyester staple fibers, 0.05%-0.15% of stannous mono-sulphate, 0.05%-0.15% of antimony trioxide and 0.15%-0.35% of a polymer binder; by adding the conductive polymer, increasing the conductivity, increasing the binding force between the active substances and between the active substances and the grid, the stability of the positive plate structure in the charging and discharging process is ensured, and the softening and falling of the lead paste are reduced, so that the charging acceptance of the positive active substance is improved, and the cycle service life of the valve-regulated power storage battery is prolonged. The conductive polymer is adsorbed on the surface of the positive electrode powder and can inhibit the growth of sulfate crystals on the surface of the electrode, thereby reducing the influence of sulfation on the service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery lead paste, and in particular relates to a formula of positive electrode lead paste for a long-life valve-regulated power battery and a preparation method thereof. Background Art

[0002] During discharge, the lead dioxide in the positive electrode of the lead-acid battery is reduced to lead sulfate. The molar volume of the generated solid lead sulfate is 92% larger than that of the lead dioxide involved in the reaction. During charging, the volume changes in the opposite way, and the volume of the plate shrinks according to the above percentage. This causes the volume of the lead paste to "pulsate" during the cycle, causing the bonding between the active substances to gradually weaken, the network structure of the active substances to become loose, and the bonding force with the grid to gradually weaken. The lead paste softens and falls off, the capacity decays, the cycle performance deteriorates, the battery fails, and the life decays.

[0003] Adding a binder is one of the ways to solve the problem of lead paste softening and falling off during the cycle of lead-acid batteries. The physical properties of the binder can optimize the overall structure of the electrode and improve the cycle performance of the battery. A cross-linked structure is formed between the electrode material and the binder, which can prevent irreversible structural changes in the electrode structure and keep the electrode structure in a stable state. An ideal binder should have good adhesion, excellent mechanical properties, stable electrochemical properties, high conductivity and other performance conditions. Therefore, multiple binders are combined into a composite binder, and the synergistic effect can effectively improve the connection between the electrode material and the binder. Summary of the invention

[0004] In view of what is mentioned in the background technology, the present invention provides a formula and preparation method for a positive lead paste of a long-life valve-regulated power storage battery containing a composite conductive polymer binder. The electrode material composite conductive polymer binder forms a cross-linked structure, which can prevent the electrode structure from undergoing irreversible structural changes and keep the electrode structure in a stable state. The conductivity is enhanced, the bonding force between the positive active materials and between the positive active materials and the grid is enhanced, the softening and shedding of the active materials are reduced, the charging acceptance of the positive active materials is improved, and the battery cycle life is increased.

[0005] The present invention solves the problems mentioned in the above background technology through the following technical means: A formula for a positive electrode lead paste of a long-life valve-regulated power storage battery containing a composite conductive polymer binder is as follows: the weight percentage of the component lead powder (containing 2%-5% red lead) is as follows: pure water 8%-12%, dilute sulfuric acid 9%-13%, high-purity graphite 0.15%-0.3%, super-strong polyester staple fiber 0.07%-0.15%, stannous sulfate 0.05%-0.15%, antimony trioxide 0.05%-0.15%, and composite conductive polymer binder 0.15%-0.35%.

[0006] As an improvement of the present invention, CMC (sodium hydroxymethyl cellulose) solid powder is added to a solvent at 20-30° C. and stirred at a speed of 200-800 rpm for 10-24 hours to obtain a CMC solution, wherein the weight percentage of CMC in the CMC solution is 0-20wt%.

[0007] As an improvement of the present invention, PEDOT:PSS (poly (3,4-ethylenedioxythiophene):polystyrene sulfonate) solid powder is added to a solvent at 20-30° C. and stirred at a speed of 200-800 rpm for 10-24 hours to obtain a PEDOT:PSS solution, wherein the weight percentage of PEDOT:PSS in the PEDOT:PSS solution is 0-20wt%.

[0008] As an improvement of the present invention, the volume ratio of the PEDOT:PSS solution and the CMC solution is (10-1000):100, and the mixture is stirred at 200-800 rpm for 10-24 hours at 20-30°C to obtain the PEDOT:PSS / CMC composite conductive polymer binder slurry for use.

[0009] As an improvement of the present invention, the solvent used to prepare the PEDOT:PSS solution and the CMC solution may be at least one of water and sulfuric acid.

[0010] As an improvement of the present invention, the composite conductive polymer binder is mixed with 50% of the formula pure water to form a slurry for use.

[0011] As an improvement of the present invention, the density of the sulfuric acid is 1.325 g / cm2-1.4 g / cm2.

[0012] As an improvement of the present invention, a process for preparing a positive electrode lead paste formula for a long-life valve-regulated power storage battery containing a composite conductive polymer binder comprises the following steps: Step 1: prepare PEDOT:PSS / CMC composite conductive polymer binder slurry according to the formula ratio, add 50% of the formula pure water and mix into a uniform slurry for standby use.

[0013] Step 2: After adding lead powder (including red) into a paste mixer, high-purity graphite, super-strong polyester staple fiber, stannous sulfate and antimony trioxide prepared according to the formula ratio are added, and dry stirring is performed for 4 to 5 minutes.

[0014] Step 3, adding uniform composite conductive polymer binder slurry, adding it into a paste mixer for wet stirring within 2 minutes, and stirring for 4 to 6 minutes.

[0015] Step 4, add the remaining 50% of the formula pure water into the paste mixer within 2 minutes for wet stirring, and stir for 4 to 6 minutes.

[0016] Step 5, after wet stirring, add dilute sulfuric acid into the paste making machine, the adding time is controlled within 5 minutes, the paste temperature is controlled between 67 and 80°C, and stirring is carried out for 12 to 14 minutes.

[0017] Step 6, when the temperature drops to 45°C, measure the apparent density, which is controlled at 4.55±0.05g / cm3. The paste is produced after the apparent density is qualified.

[0018] Step 7, the lead paste coated board prepared according to the above method is cured at a temperature of 80°C and a humidity of 100 for 4 hours, and then enters a tunnel for curing for 60 hours, and the curing temperature is controlled at 50-75°C and the humidity is 85-95, and then dried, and the drying temperature is controlled at 75°C for 16 hours, and the free lead content is detected to be less than 2%.

[0019] Compared with the prior art, the advantages of the present invention are: the formula and preparation method of the positive lead paste of a long-life valve-regulated power storage battery containing a composite conductive polymer binder of the present invention have simple process steps, no special requirements for equipment, are green and environmentally friendly, easy to implement, and suitable for large-scale promotion and application. PEDOT:PSS with general viscosity has excellent conductivity. After cross-linking and compounding with CMC, ester bonds are formed, the intermolecular binding force is increased, the adhesion is enhanced, and the conductivity is not affected; the composite conductive polymer binder is added to the positive lead paste, and the positive lead paste is evenly wrapped. Its large number of functional groups such as hydroxyl groups and ester groups make the composite conductive polymer binder, the positive active material particles, the positive active material, and the grid tightly connected, reducing the softening and shedding phenomenon of the lead paste, stabilizing the positive electrode structure, and significantly improving the cycle stability. In addition, the excellent conductivity of the composite conductive polymer binder slows down the sulfation of the positive electrode and increases the battery life. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a 100% DOD cycle curve diagram of Examples 1, 2, 3 and the control group. DETAILED DESCRIPTION

[0021] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0022] Embodiment: To make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The present invention provides the following three groups of embodiments, wherein Table 1 shows the cycle times of Embodiments 1 to 3 and a blank control group.

[0024] Table 1

[0025] Example 1: A formula for a positive electrode lead paste of a long-life valve-regulated power storage battery containing a composite conductive polymer binder, wherein the weight percentage of the lead powder component (containing 2%-5% red lead) is: Pure water 8%-12%, dilute sulfuric acid 9%-13%, high-purity graphite 0.15%-0.3%, super strong polyester staple fiber 0.07%-0.15%, stannous sulfate 0.05%-0.15%, antimony trioxide 0.05%-0.15%, composite conductive polymer binder 0.15%-0.35%.

[0026] The composite conductive polymer binder is composed of: CMC (sodium hydroxymethyl cellulose) 50%±5%, PEDOT:PSS (poly 3,4-ethylenedioxythiophene:polystyrene sulfonate) 50%±5% by weight.

[0027] The composite conductive polymer binder is mixed with 50% of the formula pure water to form a slurry for use.

[0028] The density of the sulfuric acid is 1.325±0.01 g / cm2.

[0029] Furthermore, a formula for positive electrode lead paste of a long-life valve-regulated power storage battery containing a composite conductive polymer binder comprises the following steps: Step 1: at 25° C., PEDOT:PSS (poly (3,4-ethylenedioxythiophene):polystyrene sulfonate) solid powder and CMC (sodium hydroxymethylcellulose) solid powder are added to deionized water respectively, and stirred for 4 hours to obtain a PEDOT:PSS solution and a CMC solution with a mass fraction of 2 wt%; the two solutions are mixed in a volume ratio of 1:1, and stirred at 25° C. for 12 hours to prepare a PEDOT:PSS / CMC composite binder with a concentration of 2 wt%; Step 2: Mix 0.15% of the composite conductive polymer binder with 50% of the formula pure water to form a slurry for later use.

[0030] Step 3, after adding 1000kg of lead powder (including red) into the paste mixing machine, add 2.0kg of high-purity graphite, 0.8kg of super-strong polyester staple fiber, 1.0kg of stannous sulfate and 1.0kg of antimony trioxide, and dry stir for 4-5 minutes.

[0031] Step 4, adding 56.5 kg of uniform composite conductive polymer binder slurry (the blank control group is the group without adding composite conductive polymer binder slurry), adding it into a paste mixer for wet stirring within 2 minutes, and stirring for 4 to 6 minutes.

[0032] Step 5, add 53.53 kg of pure water and add it into the paste mixer within 2 minutes for wet stirring, and stir for 4 to 6 minutes.

[0033] Step 6, after wet stirring, add 98 kg of dilute sulfuric acid with a density of 1.325 g / cm2 into the paste making machine, control the adding time to 5 minutes, control the paste temperature between 67 and 80°C, and stir for 12 to 14 minutes.

[0034] Step 7, when the temperature drops to 45°C, measure the apparent density, which is controlled at 4.55±0.05g / cm3. The paste is produced after the apparent density is qualified.

[0035] Step 8, the lead paste coated board prepared according to the above method is cured at a temperature of 80°C and a humidity of 100 for 4 hours, then enters a tunnel for curing for 60 hours, controls the curing temperature at 50-75°C and the humidity at 85-95, and is dried at a controlled drying temperature of 75°C for 16 hours, and the free lead content is detected to be less than 2%.

[0036] Example 2: A formula for a positive electrode lead paste of a long-life valve-regulated power storage battery containing a composite conductive polymer binder, comprising the following steps: Step 1: at 25° C., PEDOT:PSS (poly (3,4-ethylenedioxythiophene):polystyrene sulfonate) solid powder and CMC (sodium hydroxymethylcellulose) solid powder are added to deionized water respectively, and stirred for 4 hours to obtain a PEDOT:PSS solution and a CMC solution with a mass fraction of 2 wt%; the two solutions are mixed in a volume ratio of 1:1, and stirred at 25° C. for 12 hours to prepare a PEDOT:PSS / CMC composite binder with a concentration of 2 wt%; Step 2: Mix 0.25% of the composite conductive polymer binder with 50% of the formula pure water to form a conductive polymer binder slurry for later use.

[0037] Step 3, after adding 1000kg of lead powder (including red) into the paste mixing machine, add 2.0kg of high-purity graphite, 1.0kg of super-strong polyester staple fiber, 1.0kg of stannous sulfate and 1.0kg of antimony trioxide, and dry stir for 4-5 minutes.

[0038] Step 4, add 57.5 kg of uniform composite conductive polymer binder slurry, add it into a paste mixer within 2 minutes for wet stirring, and stir for 4 to 6 minutes.

[0039] Step 5, add 52.55 kg of pure water and add it into the paste mixer within 2 minutes for wet stirring, and stir for 4 to 6 minutes.

[0040] Step 6, after wet stirring, add 98 kg of dilute sulfuric acid with a density of 1.325 g / cm2 into the paste making machine, control the adding time to 5 minutes, control the paste temperature between 67 and 80°C, and stir for 12 to 14 minutes.

[0041] Step 7, when the temperature drops to 45°C, measure the apparent density, which is controlled at 4.55±0.05g / cm3. The paste is produced after the apparent density is qualified.

[0042] Step 8, the lead paste coated board prepared according to the above method is cured at a temperature of 80°C and a humidity of 100 for 4 hours, then enters a tunnel for curing for 60 hours, controls the curing temperature at 50-75°C and the humidity at 85-95, and is dried at a controlled drying temperature of 75°C for 16 hours, and the free lead content is detected to be less than 2%.

[0043] Example 3: A formula for a positive electrode lead paste of a long-life valve-regulated power storage battery containing a composite conductive polymer binder, comprising the following steps: Step 1: at 25° C., PEDOT:PSS (poly (3,4-ethylenedioxythiophene):polystyrene sulfonate) solid powder and CMC (sodium hydroxymethylcellulose) solid powder are added to deionized water respectively, and stirred for 4 hours to obtain a PEDOT:PSS solution and a CMC solution with a mass fraction of 2 wt%; the two solutions are mixed in a volume ratio of 1:1, and stirred at 25° C. for 12 hours to prepare a PEDOT:PSS / CMC composite binder with a concentration of 2 wt%; Step 2: Mix 0.35% of the composite conductive polymer binder with 50% of the formula pure water to form a slurry for later use.

[0044] Step 3, after adding 1000kg of lead powder (including red) into the paste mixing machine, add 2.0kg of high-purity graphite, 0.8kg of super-strong polyester staple fiber, 1.0kg of stannous sulfate and 1.0kg of antimony trioxide, and dry stir for 4-5 minutes.

[0045] Step 4, add 58.5 kg of uniform composite conductive polymer binder slurry, add it into a paste mixer within 2 minutes for wet stirring, and stir for 4 to 6 minutes.

[0046] Step 5, add 51.57 kg of pure water into the paste mixer within 2 minutes for wet stirring, and stir for 4 to 6 minutes.

[0047] Step 6, after wet stirring, add 98 kg of dilute sulfuric acid with a density of 1.325 g / cm2 into the paste making machine, control the adding time to 5 minutes, control the paste temperature between 67 and 80°C, and stir for 12 to 14 minutes.

[0048] Step 7, when the temperature drops to 45°C, measure the apparent density, which is controlled at 4.55±0.05g / cm3. The paste is produced after the apparent density is qualified.

[0049] Step 8, the lead paste coated board prepared according to the above method is cured at a temperature of 80°C and a humidity of 100 for 4 hours, then enters a tunnel for curing for 60 hours, controls the curing temperature at 50-75°C and the humidity at 85-95, and is dried at a controlled drying temperature of 75°C for 16 hours, and the free lead content is detected to be less than 2%.

[0050] The above embodiments are only used to illustrate the technical solutions of the present invention and are not used to limit the present invention. Although the present invention is described in detail through the above embodiments, it is possible for those skilled in the art to make other changes in details and forms without departing from the contents defined in the claims of the present invention and all of them belong to the scope of protection of the present invention.

Claims

1. A formula for positive lead paste of a long-life valve-regulated power battery, characterized in that: The formula includes components as follows: lead powder, wherein the lead powder contains 2%-5% red lead, 8%-12% by weight of pure water, 9%-13% by weight of dilute sulfuric acid, 0.15%-0.3% by weight of high-purity graphite, 0.07%-0.15% by weight of super-strong polyester staple fibers, 0.05%-0.15% by weight of stannous sulfate, 0.05%-0.15% by weight of antimony trioxide, and 0.15%-0.35% by weight of a polymer binder.

2. A long-life valve-regulated power battery positive electrode lead paste formula according to claim 1, characterized in that: The composite conductive polymer binder is PEDOT:PSS / CMC, and the composite conductive polymer binder is added into the positive electrode lead paste formula.

3. A method for preparing the positive electrode lead paste formula of a long-life valve-regulated power storage battery according to claim 1 or 2, characterized in that: The following steps are involved: Step 1, after adding the lead powder containing red into a paste mixing machine, high-purity graphite, super-strong polyester staple fiber, stannous sulfate and antimony trioxide configured according to the formula ratio are added, and dry stirring is performed; Step 2, adding the composite conductive polymer binder and 10%-50% of formula water to a slurry mixed and stirred, and adding the slurry into a paste mixer for wet stirring; Step 3, add the remaining 50%-90% of the formula pure water into the paste making machine for wet mixing; Step 4, after wet stirring, add dilute sulfuric acid to the paste machine, control the adding time, control the paste temperature between 67 and 80°C, and stir; Step 5, when the temperature drops, measure the apparent density, and produce the paste after the apparent density is qualified; Step 6, the lead paste coated board prepared according to the above method is cured under appropriate temperature and humidity conditions, and then enters a tunnel curing, controls the curing temperature and humidity for drying, controls the drying temperature and time, and detects that the free lead content is less than 2%.

4. The method for preparing positive electrode lead paste for long-life valve-regulated power storage battery according to claim 2, characterized in that: In the method, a PEDOT:PSS solution and a CMC solution are mixed and cross-linked to obtain the PEDOT:PSS / CMC composite adhesive.

5. The method for preparing positive electrode lead paste for long-life valve-regulated power storage battery according to claim 4, characterized in that: The PEDOT:PSS / CMC composite binder was prepared according to the following steps: Step 1, adding CMC solid powder into a solvent at 20-30° C. and stirring to obtain a CMC solution, wherein the weight percentage of CMC in the CMC solution is 0-20wt%; Step 2, adding PEDOT:PSS solid powder into a solvent at 20-30° C. and stirring to obtain a PEDOT:PSS solution, wherein the weight percentage of PEDOT:PSS in the PEDOT:PSS solution is 0-20wt%; Step 3, the volume ratio of the PEDOT:PSS solution and the CMC solution is (10-1000):100, and stirring and mixing at 20-30°C to obtain the PEDOT:PSS / CMC composite conductive polymer binder for standby use; Step 4: The solvent used to prepare the PEDOT:PSS solution and the CMC solution is at least one of water and sulfuric acid.

6. The positive electrode lead paste formula of a long-life lead-acid battery according to claim 5, characterized in that: The density of the sulfuric acid is 1.325 g / cm2-1.4 g / cm2.

Citation Information

Patent Citations

  • Natural polymer derivative-conducting polymer aqueous composite binder and application thereof

    CN103396500A

  • PEDOT: PSS / CMC composite binder and preparation method and application thereof

    CN110890545A

  • Long-life valve control type power storage battery positive electrode lead paste, preparation method and storage battery

    CN117497762A

  • Highly efficient electrodes enabled by segregated networks

    US20230216058A1

  • Modified current collector for secondary battery

    WO2023230872A1

Cited By

  • High-temperature-resistant lead-acid storage battery positive plate and preparation method thereof

    CN121839583A